Search Frictions and the Labor Wedge - Andrea Pescatori; Murat Tasci (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This paper assesses whether labor market frictions, in the form of searching and matching, can help explain movements in the labor wedge - the gap between the marginal rate of substitution (MRS) and the marginal productivity of labor in a perfectly competitive business cycle model. Results suggest that those frictions are not able to explain fluctuations in the labor wedge, per se. However, the introduction of extensive and intensive margin shows that measuring the MRS in terms of total hours artificially introduces procyclicality in the MRS. When the MRS is correctly measured in terms of hours per worker, the labor wedge obtained is less variable than the one of the perfectly competitive model. A Frisch elasticity of 2.8, as in most macro models, implies a 20 percent decline in the variability of the labor wedge. A Frisch elasticity closer to micro estimates implies an even higher reduction. Finally, we show that it is possible to measure a strongly procyclical labor wedge as in CKM (2007) even if the actual data generating process does not have any labor wedge but has search frictions that allow for movements in both labor margins.
Keywords: E24; E32; J64; 330; Labor Market Search; Business Cycle Accounting; Labor Wedge; Suchtheorie; Arbeitsproduktivität; Kapazitätsauslastung; Vollkommener Wettbewerb; Konjunkturtheorie